2004
DOI: 10.1111/j.1468-3083.2004.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Videodermatoscopy enhances the ability to monitor efficacy of scabies treatment and allows optimal timing of drug application

Abstract: VD enhances the monitoring of clinical response to treatment and allows optimal timing of drug application. This may be particularly important in minimizing risk of overtreatment, reducing the potential for side-effects, and enhancing patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…First, it does not allow egg visualization; however, this limitation did not prevent us from obtaining a high sensitivity. Second, at this low magnification, the viability of the mite cannot be assessed; however, this is not a concern in previously untreated patients, and in previously treated patients, posttherapeutic monitoring studies using high-magnification DS have suggested that dying mites lose their actual shape 14,17 ; it is, therefore, likely that, even in previously treated patients, the characteristic circumflex accentlike image is seen only if the mite is viable. Third, since fomites may survive in the environment for up to 72 hours, indirect contamination through the DS might occur; careful disinfection of the device after each examination should be emphasized.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…First, it does not allow egg visualization; however, this limitation did not prevent us from obtaining a high sensitivity. Second, at this low magnification, the viability of the mite cannot be assessed; however, this is not a concern in previously untreated patients, and in previously treated patients, posttherapeutic monitoring studies using high-magnification DS have suggested that dying mites lose their actual shape 14,17 ; it is, therefore, likely that, even in previously treated patients, the characteristic circumflex accentlike image is seen only if the mite is viable. Third, since fomites may survive in the environment for up to 72 hours, indirect contamination through the DS might occur; careful disinfection of the device after each examination should be emphasized.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12]14,15,17 Under the highest magnifications, the 0.2 to 0.4 mmelong S scabiei's substructures can be seen; eggs and feces are also visible. At 403 magnification a ''jet with contrail''-like mite image has been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need to develop better tools to monitor for drug resistance in order to monitor and define the extent of resistance in scabies mites. Videodermatoscopy has lately been described as a successful method for in vivo monitoring of drug effectiveness, with observations post treatment demonstrating the reduced-migration ability and eventual death of the mite under the skin [15]. However, continued epidemiologic studies and the development of molecular tools will identify the factors which govern the emergence and spread of resistant strains of S. scabiei.…”
Section: Chemotherapymentioning
confidence: 98%
“…Epiluminescence microscopy and high-resolution videodermatoscopy are noninvasive techniques that allow detailed inspection of the patient's skin, from the surface to the superficial papillary dermis (2,49,80). Diagnosis is by observations of the "jet-with-contrail" pattern in the skin representing a mite and its burrow.…”
Section: Dermatoscopymentioning
confidence: 99%